2019
DOI: 10.3390/su11030917
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Indicators for Startup Business Success: Sentiment Analysis Using Text Data Mining

Abstract: The main aim of this study is to identify the key factors in User Generated Content (UGC) on the Twitter social network for the creation of successful startups, as well as to identify factors for sustainable startups and business models. New technologies were used in the proposed research methodology to identify the key factors for the success of startup projects. First, a Latent Dirichlet Allocation (LDA) model was used, which is a state-of-the-art thematic modeling tool that works in Python and determines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 45 publications
3
151
0
2
Order By: Relevance
“…Normally, accessing and analyzing these databases is imprecise, expensive and time-consuming. [1,2] Furthermore, as the use of these technologies has become habitual for users, it has also become commonplace for users to share information about individual experiences and opinions, as well as content related to the interests of users and companies via social networks. In looking at these types of 2 of 13 data sources, several studies have analyzed the influence of the application of strategies of business intelligence (BI) on business models [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, accessing and analyzing these databases is imprecise, expensive and time-consuming. [1,2] Furthermore, as the use of these technologies has become habitual for users, it has also become commonplace for users to share information about individual experiences and opinions, as well as content related to the interests of users and companies via social networks. In looking at these types of 2 of 13 data sources, several studies have analyzed the influence of the application of strategies of business intelligence (BI) on business models [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The time horizon analyzed was from 10-17 June 2019, allowing the download of a total of n = 10,786 tweets under the search term #Education. Following Sherman et al [39] and Banerjee et al [40], we used a randomized controlled process to select this term by focusing on the education sector and the proposed research questions. This process allows researchers to systematically select a sample based on the social media content-in this study, in the form of tweets with a specific hashtag.…”
Section: Data Sampling Extraction and Collectionmentioning
confidence: 99%
“…For each review, we selected the features according to the principal feature list. Other methods, such as the latent Dirichlet allocation (LDA) model presented in the work of Saura et al [54], can be used to extract the main features.…”
Section: Product Feature Selection Stagementioning
confidence: 99%
“…A network-based feature selection method, that is, feature relation networks (FRNs), helped to improve the performance of the classifier. Saura et al [54] identified key factors in UGC for the creation of successful start-ups by analyzing sentiments with an SVM. This method was applied to identify the start-up topics via the polarity sentiment.…”
Section: Introductionmentioning
confidence: 99%